The Professional Practice of the Social Worker’s Role between Reality and Challenges: A Descriptive Study on A Sample of Social Workers at Health Institutions in Yanbu - 2023 - Abu Shurayyan, Suhayb Mousa (Journal of Humanities & Social Sciences, 2024)
The main objective of the current study is to identify the reality of social workers practicing their actual professional roles within the Yanbu government and private health institutions and the Royal Commission Medical Center, from that main goal emerges a group of sub-goals, namely identifying the professional roles of social workers in health institutions in Yanbu, revealing the current tasks of social workers in health institutions in Yanbu, and identifying the skills that social workers have in health institutions in Yanbu, in addition to listing the challenges Which hinders social workers from exercising their professional roles in health institutions in Yanbu. The current study belongs to the descriptive studies that aim to identify the reality of social workers practicing their actual professional roles within the government and private health institutions in Yanbu and the medical center affiliated with the Royal Commission in Yanbu. The study relied on the sample social survey approach, where the researcher visited hospitals and obtained the number of working social workers. At the General Hospital in Yanbu Governorate, the Medical Center of the Royal Commission, and private hospitals in Yanbu Governorate, then obtaining means of communication with these social workers. After that, the researcher distributed the electronic questionnaire to all social workers, as the number of respondents to the questionnaire was (63) social workers, out of (88) social workers. Social workers working in Yanbu Governorate in these three sectors (the Royal Commission Medical Center, Yanbu General Hospital, and private hospitals in Yanbu. The most prominent results of the current study were that the general trend in the role of the social worker is high, with an arithmetic average of (4.1) out of (5). Most of the sample members agreed that the social worker works to develop the patient’s abilities to overcome difficulties, in addition to the specialist The social worker provides professional advice about hospital services in the first place.